Does smoking interfere with the effect of histamine H2-receptor antagonists on intragastric acidity in man?. Issue 5 (May 1987) - Bauerfeind, P; Cilluffo, T; Fimmel, C J; Emde, C; von Ritter, C; Kohler, W; Gugler, R; Gasser, T; Blum, A L
Abstract : The interaction between smoking and the effect of histamine H2-antagonists on intragastric acidity was examined in a double blind double dummy placebo controlled study. Healthy volunteers, 11 smokers and 10 non-smokers, were given, on four separate days at least one week apart, either placebo or cimetidine 800 mg nocte or ranitidine 2 X 150 mg per day or ranitidine 300 mg nocte. Tablets were taken at 2115 and 0900 h. Smokers smoked a cigarette hourly from 0700 to 2300 h. Breakfast, lunch, and dinner were standardised. Intragastric acidity was measured with a combined intragastric glass electrode and a solid state recorder. The subjects were fully ambulatory. The three histamine H2-receptor antagonist regimens were less effective (p = 0.04) in smokers than in non-smokers, but the difference between acidity of smokers and non-smokers was small. Means of medians of pH during a 24-h period with placebo, cimetidine 800 mg, ranitidine 2 X 150 mg and ranitidine 300 mg were 1.6, 2.3, 3.1, and 2.7 in smokers and 1.5, 2.7, 3.2, and 3.1 in non-smokers, respectively. In a second part of the study seven chronic smokers were reexamined after acutely stopping smoking: inhibition of gastric acidity by histamine H2-receptor antagonists was similar before and after withdrawal. Smoking does not affect intragastric acidity in untreated volunteers and only slightly decreases the effectiveness of histamine H2-receptor antagonists on intragastric acidity. This effect best in part explains the unfavourable effect of smoking on healing of peptic ulcer in patients treated with these drugs.